Metabolomics reveals the mechanisms of action of fosfomycin and azithromycin combination in the treatment of Pseudomonas aeruginosa - Zhao, Ziyun; Diao, Shuo; Song, Meng; Cao, Xiujiao; Zhao, Yiran; Yu, Mingming; Lv, Zhihua; Sy, Sherwin K. B.; Yang, Hai (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundFosfomycin combined with other antibiotics is often used to treat Pseudomonas aeruginosa infections. In this study, we investigated the effects of fosfomycin and azithromycin as monotherapy and combination therapy on the metabolic changes of multidrug-resistant P. aeruginosa.MethodsMultidrug-resistant P. aeruginosa was exposed to fosfomycin, azithromycin, or their combination. Non-targeted metabolomic profiling was performed using LC–MS/MS. Differential metabolites were identified statistically using Student’s t-test, with significance defined as p < 0.05 and log2 fold change (log2FC) ≥ 1 or ≤ −1.ResultsThe minimum inhibitory concentration was 32/4 μg/mL for fosfomycin/azithromycin combination against the P. aeruginosa strain evaluated for metabolomic changes. Metabolomic analysis showed that the combination therapy resulted in greater disturbances affecting the abundance and content levels of metabolites of P. aeruginosa than monotherapies. The affected metabolic pathways were mainly amino acid metabolism, nucleotide metabolism, carbohydrate metabolism and lipid metabolism, among which nucleotide metabolism was most significantly disturbed. In the nucleotide metabolism, purine metabolism was affected more than pyrimidine metabolism.ConclusionFosfomycin–azithromycin combination therapy exerted stronger interference on the metabolic pathways of P. aeruginosa than either drug alone, indicating more substantial metabolic alterations at the cellular level. These findings provide mechanistic insights that may help inform the potential application of combination regimens against multidrug-resistant P. aeruginosa in the clinic.